(untitled) (Simbiótica. Revista Eletrônica, 2023)
In this article, we depart from the experiences of 21 lesbians who lived their youth between the 1960s and 1980s in Belo Horizonte as a starting point to reflect on possible contributions they may have made to the advances achieved thanks to the struggles of social movements. Despite the recent achievements of some rights and the exposure of young lesbian couples in current times, the marks, fears, care and habits common to those who carry a stigma still remain for the older ones. However, if in past times there was a lack of militancy, even so, they contributed, by aggregating in ghettos and moving around with their bodies, many of them masculine, they made their contribution, after all, the personal is and always has been, also political. Keywords: lesbianism; generations; social movements; LGBTQIA+ activism